GE_GERICHTE P/17450/2024 vom 20. November 2025 - GE Cour de justice (2025)
DROIT D'ÊTRE ENTENDU;PLAIGNANT;ABUS DE CONFIANCE;LÉSÉ;ACTIONNAIRE;DOMMAGE DIRECT;PRINCIPE DE LA TRANSPARENCE(SOCIÉTÉ) | Cst.29; CPP.115; CPP.118; CP.138